Phase Ia clinical evaluation of the plasmodium falciparum blood-stage antigen MSP1 in ChAd63 and MVA vaccine vectors - Hodgson, Susanne; Duncan, Christopher J. A.; Elias, Sean C.; Collins, Katharine A; Ewer, Katie J.; Spencer, Alexandra J.; Williams, Andrew R.; Halstead, Fenella D.; Moretz, Samuel E.; Miura, Kazutoyo; Epp, Christian; Dicks, Matthew D. J.; et al. (Molecular therapy, 2011)
Efficacy trials of antibody-inducing protein-in-adjuvant vaccines targeting the blood-stage Plasmodium falciparum malaria parasite have so far shown disappointing results. The induction of cell-mediated responses in conjunction with antibody responses is thought to be one alternative strategy that could achieve protective efficacy in humans. Here, we prepared chimpanzee adenovirus 63 (ChAd63) and modified vaccinia virus Ankara (MVA) replication-deficient vectors encoding the well-studied P. falciparum blood-stage malaria antigen merozoite surface protein 1 (MSP1). A phase Ia clinical trial was conducted in healthy adults of a ChAd63-MVA MSP1 heterologous prime-boost immunization regime. The vaccine was safe and generally well tolerated. Fewer systemic adverse events (AEs) were observed following ChAd63 MSP1 than MVA MSP1 administration. Exceptionally strong T-cell responses were induced, and these displayed a mixed of CD4+ and CD8+ phenotype. Substantial MSP1-specific serum immunoglobulin G (IgG) antibody responses were also induced, which were capable of recognizing native parasite antigen, but these did not reach titers sufficient to neutralize P. falciparum parasites in vitro. This viral vectored vaccine regime is thus a leading approach for the induction of strong cellular and humoral immunogenicity against difficult disease targets in humans. Further studies are required to assess whether this strategy can achieve protective efficacy against blood-stage malaria infection.
Gesehen am 30.11.2022